Policies, strategies and regulations on microcredentials and lifelong learning: European and Estonian framework - Shkaruba , A.; Marran , K. (Man and Environment. Issues of Neoecology, 2025)
Purpose. Analysis of key policies at both the EU and Estonian levels, including regulatory frameworks governing recognition, accreditation, and quality assurance of microcredentials. Methods. The analysis references EU-wide strategies and Estonia’s national policies, ensuring a comprehensive understanding of how microcredentials are integrated and governed. Results. Micro-credentials— short, competency-based learning units—have emerged as a promising solution for upskilling and reskilling individuals across sectors, have become a pivotal tool in modern education, especially within the European Union (EU) and Estonia, providing flexible, modular learning opportunities that address the evolving needs of individuals and industries. They serve as a bridge between formal education and workforce skill demands, offering a means for continuous professional development and lifelong learning. As policies and regulations evolve, a structured framework for microcredential recognition, accreditation, and quality assurance ensures their portability, reliability, and alignment with existing qualification systems. Conclusions. Micro-credentials in EU higher education institutions serve as a crucial tool for skill development, career progression, and academic advancement. Their design prioritizes flexibility, industry relevance, and rigorous quality assurance. Future developments will focus on enhancing stackability, improving employer engagement, and expanding digital credentialing systems to facilitate learner mobility and recognition across different sectors.